The math maze : solve your way out! : use your math skills to escape! - Wood, Alix (New York, NY : Gareth Stevens Publishing, 2023)
Whoops! You kicked your soccer ball over the wall of a mysterious math professor. Can you get it back? Not without solving some puzzles first! From geometry to prime numbers, math is the way readers can escape from the home and gardens on the math professor. Readers discover clues scattered throughout the book as they use probability, circles and degrees, and even the Fibonacci sequence to make sense of them.
A STEAM interactive puzzle book.
3.7
3-6
Keywords: Mathematics -- Juvenile literature; Puzzles; Mathematics; Puzzles; Puzzles and games; Creative nonfiction; STEAM; Escape room games. -- Juvenile literature